2020
DOI: 10.12688/f1000research.20183.3
|View full text |Cite
|
Sign up to set email alerts
|

Stage 1 Registered Report: How subtle linguistic cues prevent unethical behaviors

Abstract: Different ways of description can easily influence people’s evaluations and behaviors. A previous study by Bryan and colleagues suggested that subtle linguistic differences in ethical reminders can differentially prevent readers’ unethical behavior. The present study aims to replicate the previous finding in the Japanese context, additionally exploring the influence of unfamiliar instruction words that capture participants’ attention. In two experiments, which are planned to be conducted online, participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It was probably because our study had several limitations. One of its limitations was that it had a longer time period until data collection than previous studies [ 4 , 9 ]. In particular, in an original study [ 5 ], which had shown that people with an emphasis on self-identity were more likely to engage in voting behaviour, experimental manipulation of reminders had been conducted on the day before or the day of the voting, whereas in our study, the participants were required to perform the second wave a week after the experimental manipulation of a reminder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was probably because our study had several limitations. One of its limitations was that it had a longer time period until data collection than previous studies [ 4 , 9 ]. In particular, in an original study [ 5 ], which had shown that people with an emphasis on self-identity were more likely to engage in voting behaviour, experimental manipulation of reminders had been conducted on the day before or the day of the voting, whereas in our study, the participants were required to perform the second wave a week after the experimental manipulation of a reminder.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al . [ 9 ] calculated the effect size of the original study [ 1 ] for a value of Cohen's f = 0.302. However, the small sample size might overestimate the effect size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdsourcing. The protocol of this experiment was registered on the Open Science Framework ( Guo et al, 2020 ). The results showed that the familiarity rating score in the “cheater” condition was significantly lower than that in the “cheating” condition, t (64) = 6.73, p < .001, Cohen’s d = 0.834.…”
Section: Methodsmentioning
confidence: 99%
“…Open Science Framework: How subtle linguistic cues prevent unethical behaviors, https://doi.org/10.17605/OSF.IO/AXDHV ( Guo et al, 2020 ).…”
Section: Data Availabilitymentioning
confidence: 99%